TINJAUAN TINGKAT KESEIMBANGAN STATIS DAN DINAMIS PADA ATLET SEPATU RODA KLUB NEO INLINE SKATE DI KOTA PEKANBARU - Farid Resky; Agus Sulastio; Alimandan , (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
AbstractThis study aimed to determine the level of static and dynamic balance of roller skatingathletes at NEO Inline Skate Club in Pekanbaru City. Balance is an essential componentof physical fitness that plays a crucial role in supporting performance and reducing therisk of injury in roller skating sports. This research employed a descriptive quantitativeapproach. The population of this study consisted of all athletes of the NEO Inline SkateClub, totaling 20 athletes, with total sampling used as the sampling technique. Datacollection was conducted through tests and measurements, namely the Stork Stand Testto assess static balance and the Bass Balance Test to measure dynamic balance. Thecollected data were analyzed using descriptive statistics in the form of percentages. Theresults indicated that the static balance of the NEO Inline Skate athletes waspredominantly in the very good category (70%), while 30% were in the good category.Meanwhile, the dynamic balance level ranged from very good to sufficient, with staticbalance results generally higher than dynamic balance. It can be concluded that theathletes of the NEO Inline Skate Club possess good levels of static and dynamicbalance; however, greater emphasis is needed on improving dynamic balance throughmore specific and structured training programs.Keywords: static balance, dynamic balance, roller skating